Refuting the Alleged Innovation of Verbal and Semantic Distortion in the Holy Qur’an - خفي سعود شنيار (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The discussion on the subject of Quranic distortion revolves around what is customary in Quranic studies books, detailing its sections and highlighting its meaning in order to remove any doubts that may arise in some people. Otherwise, we believe that the Quran in the hands of Muslims now, the book they read and circulate, is the same book that was revealed to the noble Prophet Muhammad (peace be upon him and his family). It is a Quran free from any deficiency or addition, free from distortion and error. The Quran did not use the word distortion in a sense other than its linguistic meaning, i.e., manipulating the meaning of a word and interpreting it in a way other than its intended meaning, expressed by misinterpretation or interpretation based on opinion. It is a semantic distortion and nothing else. We have previously discussed the Almighty’s statement: They distort words from their [proper] usages [An-Nisa’: 46]. His statement from their [proper] usages means that after the words were used in their true meaning, which appears in themselves or was used in them based on the usual indications, then distortion came after that as a betrayal of the trust of performance and communication. In the Almighty’s statement, from their proper places [Al-Ma’idah: 41], this meaning is explicitly stated, as distortion is the displacement of a word from its proper place, which is its intended meaning. In Surah Al-Baqarah, And indeed, a party among them used to listen to the Word of Allah and then distort it after they had understood it [Al-Baqarah: 75], meaning: the distortion of the meaning to what they intended came after they had learned the true intended meaning, which, according to their claim, was contrary to their interests. Therefore, it is a form of misinterpretation, as Al-Tabarsi and before him Sheikh Al-Tibyan expressed.